ПРОБЛЕМА ФАЛЬСИФІКАЦІЇ У НАУКОВОМУ ПІЗНАННІ - Культенко, В. П.; Ничипорук, О. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Стаття присвячена дослідженню проблеми фальсифікації. В процес наукового пошуку істини во- на була введена К.Поппером, який протиставив її процедурі верифікації. В концепції К.Поппера означе- на вимога є плідною для встановлення істини. Однак це не єдиний спосіб застосування даної процедури. У протилежний спосіб вона використовується для підтасування фактів і шкодить встановленню нау- кової істини. Культенко В.П., Ничипорук А. Проблема фальсификации в научном познании. Статья по- священа исследованию проблемы фальсификации. В процесс научного поиска истины она была введена К.Поппером, который противопоставил ее процедуре верификации. В концепции К.Поппера указанное требование является плодотворным для установления истины. Однако, это не единый способ исполь- зования данной процедуры. В противовес этому она используется для подтасовки фактов и вредит ус- тановлению научной истины. Ключевые слова: фальсификация, научное познание, научная истина, философия науки, логика исследования. Kultenko V., Nichiporuk O. The problem of falsification in scientific knowledge. The article is sanctified to research of problem of falsification. To research the problem of fraud, this is a procedure for establishing the truth of a hypothesis or theory by empirical verification. In the process of scientific search for truth it was introduced by Popper, who opposed its verification procedures, believing that science critically and systematically applies the principle of falsification for uncompromising check generated theories. In concept Popper designated requirement is beneficial for establishing scientific truth. Scientists believed that the test theory or hypothesis should not be reduced to finding its logical proof, and the persistent attempts to deny it, because confirmation of the theory does not mean that it should be attributed to science. Using procedures falsification K. Popper solved the problem of the demarcation of scientific and unscientific knowledge. However, this is not the only way to apply this procedure. In the opposite way it is used for manipulation of facts and affects the establishment of scientific truth. Also know that even eminent scientists sometimes manipulated facts. It is believed that in most cases, violations of studies were forced to speed up the truth and not to hide it. In any case, a thorough analysis of the problem reveals a fraud and ethical component in its interpretation. And fraud as fraud data experiments means violation of ethnic Society, introduced by R. Merton for regulation of scientific communication between scientists. However, the progressive advancement of science is, in spite of such cases. It is the application of scientific method with falsifying test results of practical science research helps weed out fraud. Keywords: falsification, scientific knowledge, scientific truth, philosophy of science, logic research.